2021
DOI: 10.3390/opt2030014
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation on the Photothermal Properties of Luminescent Solar Concentrators

Abstract: Luminescent solar concentrators (LSCs) are considered promising photovoltaic (PV) devices to circumvent practical issues of applying conventional solar panels to the built environment. However, LSCs suffer from low power conversion efficiencies (PCEs) (typically <2% for devices of over 1 m2), despite numerous efforts having been made to develop novel luminescent materials and optical techniques. In this report, we proposed to utilize photothermal (PT) energy of the LSCs to further improve the PCE. We conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
1
Order By: Relevance
“…The total PT power of the LSC was 13.2 W, which was much higher than the P max of the LSC (1.31 W) and suggestive of a promising energy source for electric power generation in addition to the electric power from the PV conversion. Considering the PT power produced by the LSC per volume of the LSC, the PT power per volume from the LSC in this study (6.6 × 10 4 W m −3 ) was higher than that in our previous report (6.01 × 10 4 W m −3 ) [22].…”
Section: Pt Propertiescontrasting
confidence: 88%
See 1 more Smart Citation
“…The total PT power of the LSC was 13.2 W, which was much higher than the P max of the LSC (1.31 W) and suggestive of a promising energy source for electric power generation in addition to the electric power from the PV conversion. Considering the PT power produced by the LSC per volume of the LSC, the PT power per volume from the LSC in this study (6.6 × 10 4 W m −3 ) was higher than that in our previous report (6.01 × 10 4 W m −3 ) [22].…”
Section: Pt Propertiescontrasting
confidence: 88%
“…Therefore, it is of great importance to study the PT properties of LSCs and find solutions to utilize the PT energy. Recently, our team performed a preliminary investigation of the PT properties of LSCs through Monte Carlo ray-tracing simulations [22]. We showed that the PCE could also be improved through the utilization of PT energy by thermoelectric devices that have been widely developed [23][24][25].…”
Section: Introductionmentioning
confidence: 99%